Effect of midwifery students’ continuity of care program on women’s experiences of maternity care: A randomised controlled trial - Elham Jafari; Mojgan Mirghafourvand; Shamsi Abbasalizadeh; Shahla Meedya; Leila Doshmangir; Sakineh Mohammad-Alizadeh-Charandabi (PLoS ONE, 2026)
Background Midwifery continuity of care (CoC) benefits women and families. Engaging midwifery students may help extend such care and improve access to quality maternity services. This study evaluated the impact of a student-led CoC on women’s maternity care experiences during childbirth in a middle-income country. No trials to date have assessed these effects. Methods We conducted a randomized controlled trial with low-risk pregnant women at 26–29 weeks of gestation, intending vaginal delivery. Participants were randomized to intervention (n = 45) or control (n = 48) groups through stratified block randomization with central allocation concealment. The intervention group received continuous care from final-year midwifery students, while both groups received usual care. Childbirth experiences were assessed 40−50 days postpartum using the Childbirth Experience Questionnaire (CEQ-2), while secondary outcomes were measured with the Experience of Maternity Care and Maternal Satisfaction scales. Results All recruited women were followed up, and baseline characteristics were comparable. In the intervention group, 12 women (27%) had caesarean sections compared to 18 women (38%) in the control group. Among women with experience of labour pain at the hospital (37 intervention, 35 control), the intervention group reported higher mean childbirth experience scores (3.3 vs. 2.3; adjusted mean difference [AMD] 1.03, 95% confidence interval [CI] 0.8 to 1.3). The intervention group scored higher in maternity care experiences during pregnancy (AMD 15.7; 95% CI 13.3 to 18.2), labour and birth (35.6 vs. 23.0; AMD 12.6, 95% CI 7.9 to 17.4), and postnatal care (45.1 vs. 28.2, AMD 17.1; 95% CI 14.0 to 20.2). Maternal satisfaction was greater for normal (187 vs. 130; AMD 56, 95% CI 45–68) and caesarean (162 vs. 130, AMD 30, 95% CI 11–50) births among women in the intervention group. Conclusions Undergraduate midwifery students were able to provide CoC that improved women’s experiences of maternity care. These findings are promising for further research and practical implementation. Trial registration Iranian Registry of Clinical Trials, IRCT20100414003706N41, registered prospectively on 30 April 2022, https://trialsearch.who.int/Trial2.aspx?TrialID=IRCT20100414003706N4 1; https://irct.behdasht.gov.ir/trial/62761 .